2022
DOI: 10.1186/s12951-022-01349-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumor accumulation and therapeutic efficacy of liposomal drugs through over-threshold dosing

Abstract: Background Most intravenously administered drug-loaded nanoparticles are taken up by liver Kupffer cells, and only a small portion can accumulate at the tumor, resulting in an unsatisfactory therapeutic efficacy and side effects for chemotherapeutic agents. Tumor-targeted drug delivery proves to be the best way to solve this problem; however, the complex synthesis, or surface modification process, together with the astonishing high cost make its clinical translation nearly impossible. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In all literature, ,,, blank nanoparticles with a single particle size were used to verify the feasibility of the threshold theory. Therefore, this project intends to investigate whether changes in the size of BSA-NPs affect the in vivo distribution of LIBOD.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In all literature, ,,, blank nanoparticles with a single particle size were used to verify the feasibility of the threshold theory. Therefore, this project intends to investigate whether changes in the size of BSA-NPs affect the in vivo distribution of LIBOD.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The ex vivo imaging of tissues clearly showed that X-CBMs exhibited a remarkable accumulation in tumors (4.4- and 3.9-fold compared to CBMs and X-PEGMs, respectively) and low distribution in normal organs (Figure C,D), leading to a significantly higher tumor-to-normal tissue (T/N) ratio (Table S4). Moreover, it should be noted that X-PEGM was primarily accumulated in the liver and spleen in contrast to the tumors or other organs, indicating that the majority of X-PEGM was eliminated by the reticuloendothelial system (RES) accompanied by the liver/spleen toxicity for long-term use of PEG formulations. …”
Section: Resultsmentioning
confidence: 99%
“…Hui Ao et al. ( 2022 ) fabricated Annona squamosa seed oil (ASSO) into nanoparticles using TPGS as a stabilizer. ASSO was mainly composed of OA and linoleic acid, together with a small amount of stearic acid and palmitic acid, of which unsaturated fatty acids account for about 70%.…”
Section: Resultsmentioning
confidence: 99%